Lectotype designation for Scilla undulata Desf. (Asparagaceae) from among the mixed original material - Crespo, Manuel B.; Martínez-Azorín, Mario; Alonso-Vargas, Mª Ángeles (Phytotaxa, 2019)
Scilla undulata Desfontaines (1792: 161) was described for plants occurring in Barbary, namely on the northern coastal areas of Tunisia and Algeria. The name has been applied to hysteranthous plants with undulate, glabrous leaves; inflorescence long racemose, usually loose; flowers pedicellate, stellate, with small, shortly spurred, deciduous bracts; perigone lobes linear to subspatulate, shortly fused at base, pinkish with a darker central band; capsules subquadrate to obovate-elliptic in outline, trigonous, appressed to the axis; seeds numerous, blackish, shinning, flattened, broadly winged (Maire 1958, Rico 2013). It is widespread mostly in the low land of the southern Mediterranean basin, from western Morocco to the Middle East, extending to southeastern Iberian Peninsula, Corsica and Sardinia (McNeill 1980, Tison & Foucault 2014, Bartolucci et al. 2018).